On assuming Mean Radiant Temperature equal to air temperature during PMV-based thermal comfort study in air-conditioned buildings - Chaudhuri, Tanaya (2017)
Mean Radiant Temperature (MRT) is an important factor of Fanger's PMV model, which is the most popular method to study human thermal comfort. However, it has often been a practice to assume MRT equal to air temperature (Ta) during indoor thermal studies. In this paper, we have studied the consequences of this simplistic assumption on the thermal comfort of occupants in air-conditioned buildings. A worldwide database of about 10000 occupants covering 9 climatic zones and 4 seasons has been studied. The effect on comfort indices-Predicted Mean Vote (PMV), Actual Mean Vote (AMV), Thermal Acceptability Vote (TSA) and Thermal Preference Vote (MCI) are presented. It is observed that even a small difference in Ta and MRT can lead to significant error in determination of thermal comfort. A correlation study between AMV and the six Macpherson factors reveals that MRT has the highest positive correlation with the thermal sensation reported by the occupants. Study of TSA and MCI show that the assumption is more likely to affect comfort level determination in the uncomfortable range.